A alfabetização científica no ensino de Ciências no 5º ano do ensino fundamental em uma escola de tempo integral no município de Manaus/AM. - Melo, Rafael de Azevedo (2017)
This dissertation with the theme The Scientific Literacy in the Teaching of Sciences in the 5th year of Elementary School in a School of Integral Time in the city of Manaus / AM, linked to the Postgraduate Program in Education and Teaching of Sciences in the Amazon, by the State University of Amazonas, is guided by the following scientific problem: how is the process of Scientific Literacy in Science Teaching developed in a class of the 5th year of Elementary School in a School of Integral Time in the City of Manaus? For this purpose, we have outlined the general objective: to understand how the process of Scientific Literacy in Science Teaching is developed in a group of the 5th year of Elementary School in a School of Integral Time in the City of Manaus. In order for us to achieve this goal, we draw the following specific objectives: Identify the theoretical-practical foundations of scientific literacy and science teaching; To know the conceptions of scientific literacy and science teaching expressed in the pedagogical proposal of the School of Integral Time and of the subjects researched; To analyze the pedagogical practice of the teacher, the use of the spaces and / or resources used in the science classes that can favor the Scientific Literacy. Our methodological approach was based on the qualitative approach, where we used interviews, observation and documentary research, and content analysis guided the analysis procedures. In the results and discussions indicated that the pedagogical practice, well developed and intentional, in Science Teaching, based on connections with natural phenomena, sociocultural and the training of students for the full exercise of citizenship, with a view to their social well-being, provided possibilities in the process of Scientific Literacy, developing students' scientific skills, such as observing and elaborating hypotheses through systematized thoughts. We verified the indicators of Scientific Literacy, pointed out in the work of Sasseron and discussed in our research. Keywords: Scientific Literacy. Science teaching. Pedagogical Practice. Learning